Interfaces Between Cathode and Electrolyte in Solid State Lithium Batteries: Challenges and Perspectives - Nie, Kaihui; Hong, Yanshuai; Qiu, Jiliang; Li, Qinghao; Yu, Xiqian; Li, Hong; Chen, Liquan (Frontiers in Chemistry, 2018)
Solid state lithium batteries are widely accepted as promising candidates for next generation of various energy storage devices with the probability to realize improved energy density and superior safety performances. However, the interface between electrode and solid electrolyte remain a key issue that hinders practical development of solid state lithium batteries. In this review, we specifically focus on the interface between solid electrolytes and prevailing cathodes. The basic principles of interface layer formation are summarized and three kinds of interface layers can be categorized. For typical solid state lithium batteries, a most common and daunting challenge is to achieve and sustain intimate solid-solid contact. Meanwhile, different specific issues occur on various types of solid electrolytes, depending on the intrinsic properties of adjacent solid components. Our discussion mostly involves following electrolytes, including solid polymer electrolyte, inorganic solid oxide and sulfide electrolytes as well as composite electrolytes. The effective strategies to overcome the interface instabilities are also summarized. In order to clarify interfacial behaviors fundamentally, advanced characterization techniques with time and atomic-scale resolution are required to gain more insights from different perspectives. And recent progresses achieved from advanced characterization are also reviewed here. We highlight that the cooperative characterization of diverse advanced characterization techniques is necessary to gain the final clarification of interface behavior, and stress that the combination of diverse interfacial modification strategies is required to build up decent cathode-electrolyte interface for superior solid state lithium batteries.